FAA A320 Type Rating and Employment Prospects of Low-Time Pilots in the Global Aviation Labor Market - Gema Merdeka Goeyardi (CV. Sutan Mandiri Sejahtera, 2026)
This study investigates the impact of holding an FAA A320 type rating on the employability of newly graduated pilots in the global aviation labor market over the period 2005–2025. Using panel data and econometric methods, including correlation analysis and fixed versus random effects models, the findings demonstrate that possession of an A320 type rating significantly enhances employment prospects, even for pilots with limited flight hours. Regional comparisons across North America, Asia Pacific, and Europe reveal variations in recruitment preferences, but consistently show that certification mitigates the disadvantage of low flight experience. The results suggest that tailored training programs, financial support for certification, and harmonized regulatory frameworks are essential to strengthen pilot competitiveness and workforce sustainability. In addition, the study outlines an advanced research agenda employing Computable General Equilibrium (CGE) modeling to assess the broader macroeconomic implications of pilot training and certification policies, including their effects on employment, economic growth, and environmental sustainability. By integrating perspectives on employability, labor crises, and technological change, this research provides valuable insights for policymakers, industry stakeholders, and training institutions in shaping a more competitive and resilient aviation workforce.